TMS 2011, 140th Annual Meeting & Exhibition, Supplemental proceedings. Volume 2, (Minerals, Metals and Materials Society ; Wiley, 2011)
Collection of papers representing 13 symposia from the meeting.
Keywords: Materials -- Congresses.; Materials science -- Congresses.; Nanostructured materials -- Congresses.; Alloys -- Congresses.; elektronické knihy; electronic books